Unit roots and structural breaks - Perron, Pierre 1959- (MDPI, 2018)
This book deals with problems related to unit roots and structural change, and the interplay between the two. The research agenda dealing with these topics have proved to be of importance to devise procedures that are reliable for inference and forecasting. Several important contributions have been made. Still, there is scope for improvements to and analyses of the existing procedures. This book provides contributions that follow up on what has been done and/or offer new perspectives on such issues and related ones.
This edition is a reprint of the special issue published online in the open access journal Econometrics (ISSN 2225-1146) from 2016-2017 (available at: http://www.mdpi.com/journal/econometrics/special_issues/unit_roots_structural_breaks).
Keywords: Aufsatzsammlung